One-and-a-half nostril versus binostril endoscopic transsphenoidal approach to the pituitary adenomas: A prospective randomized controlled trial - Zhu, Junhao; Wen, Guodao; Tang, Chao; Cong, Zixiang; Cai, Xiangming; Yang, Jin; Ma, Chiyuan (Frontiers in Surgery, 2022)
Background: Binostril endoscopic transsphenoidal approach (BETA) is the most used approach for sellar lesions nowadays, while its damage to the nasal structures may cause nasal discomfort and affect nasal functions including respiration and olfaction. With the purpose to improve the post-operative sinonasal quality of life (QoL), we introduced the one-and-a-half nostril endoscopic transsphenoidal approach (OETA) in 2016 which preserved more natural structures and registered a prospective randomized controlled trial (ChiCTR-IOR-16008222) to compare the two approaches regarding the surgical outcomes and complications. Methods: Sixty patients with pituitary adenomas were recruited and randomly assigned to the OETA group and the BETA group between April 2016 and May 2017 in Jinling Hospital. The tumor resection rate, endocrinal and visual outcomes, and surgical complications between the OETA and BETA groups were analyzed. Besides, the questionnaire Anterior Skull Base Nasal Inventory-12 (ASK Nasal-12) was used to evaluate patients’ sinonasal QoL at seven time points (pre-operative; 2-weeks, 1-month, 3-months, 6-months, 12-months, and long-term post-operatively). The Sniffin’ Sticks were used to assess patients’ olfactory function objectively in a long term. Each patient was followed for at least 12 months post-operatively. Results: There was no significant difference in tumor resection rate, hormonal and visual outcomes, and surgical complications between the two groups. Regarding the ASK Nasal-12, patients in the OETA group complained less about dried nasal material at 2 weeks after surgery (P=0.017). One month after surgery, the OETA group had better olfaction function (P=0.019) compared with the BETA group. However, there was no significant difference in early and long-term postoperative sinonasal QoL between the two approaches according to the entire ASK Nasal-12 metric. The results of the Sniffin’ Sticks showed that the two groups had a similar olfactory performance at long-time follow-up. Conclusion: In this single tertiary center trial, the results showed that the OETA achieved the same surgical outcomes and post-operative sinonasal QoL as the BETA.